Pria 19 Tahun dengan Ginekomastia Unilateral: Laporan Kasus - Angrella, Noviane; Hanifah, Lika; Pariding, Imanuel Taba (Cermin Dunia Kedokteran, 2025)
Introduction: Gynecomastia is a condition of breast enlargement in men due to breast gland proliferation that is generally bilateral. Unilateral gynecomastia is rarely found in young adults. Case: A 19-year-old male presenting with right breast enlargement noticed within the past month. There was no pain, no breast discharge, and no hard lump when palpated. On physical examination, the right breast was larger than the left breast, without skin changes (peau d’orange, ulceration), nipple retraction, or any discharge. Glandular enlargement with a diameter of +5 cm, painless, tender, immobile, firm borders, no galactorrhea, no palpable lumps. Laboratory examination was within normal limits. The diagnosis was unilateral right gynecomastia. A simple mastectomy was performed on the right breast. Histopathologic findings supported the diagnosis of gynecomastia. Conclusion: Anamnesis and physical examination can establish the diagnosis of gynecomastia. Further laboratory and imaging evaluations are required to substantiate clinical suspicion or in unclear cases and to search for underlying causes.